Effectiveness of Aerobic Exercise on Obesity among Adolescents: A Study from Western Maharashtra - Bhosale, Tejas S.; Potdar, Nutan J.; Choudhari, Samir K. (Journal of Neonatal Surgery, 2025)
Introduction: Obesity has become a widespread global epidemic, prompting the World Health Organization to express concern about its increasing prevalence, which poses risks for non-communicable diseases in many nations. Material and Methods: One group pre-test and post-test experimental research design conducted on Secondary school going students. Ethical clearance was obtained from the ethical committee and a total of nine schools were selected for the study. The sample comprised 127 adolescents, and both the adolescents' assent and their parents' consent were obtained. The respondents were assured that their information would remain anonymous and confidential. The researcher then gathered the data, which included socio-demographic variables from the adolescents, as well as pre-test anthropometric measurements were assessed. Over a period of three months, the adolescents participated in aerobic exercises, which lasted 45 minutes per session, including 15 minutes for warm-up, 30 minutes for exercise, and 15 minutes for cool-down. These sessions were held three times a week. After three months, a post-test was administered to assess obesity. Results: The present study result shows that pre-test mean of the height, Body Weight, the Body Mass Index, Waist Circumference, and Mid Arm Circumference found significantly difference compare to post-test at the level of p<0.0001. Conclusion: The findings indicate that physical activity can significantly reduce obesity among Secondary School Students